Real-time imaging of cortical areas involved in the generation of increases in skin sympathetic nerve activity when viewing emotionally charged images - Henderson, Luke A.; Stathis, Alexandra; James, Cheree; Brown, Rachael; McDonald, Skye; Macefield, Vaughan G. (NeuroImage (Orlando, Fla.), 2012)
The sympathetic innervation of the skin not only primarily subserves thermoregulation, but has also been commandeered as a means of emotional expression. While the majority of brain imaging studies of emotion have utilised the galvanic skin response as a means of inferring changes in skin sympathetic nerve activity (SSNA), spontaneous fluctuations in the galvanic skin response bear little relation to spontaneous fluctuations in SSNA. To improve our understanding of the central neural processes involved in the generation of autonomic emotional markers, we recorded SSNA concurrently with brain functional magnetic resonance imaging in 13 subjects. Emotional changes were evoked by presentation of positively-charged (erotica) or negatively-charged (mutilation) images from the International Affective Picture System. Positive and negative emotionally-charged images evoked significant increases in total SSNA and signal intensity in the orbital, dorsolateral and ventromedial prefrontal cortices, amygdala, nucleus accumbens and anterior insula. Increases in signal intensity during increases in SSNA occurred in a number of brain regions, including the central and lateral amygdala, dorsolateral pons, thalamus, nucleus accumbens, and cerebellar cortex. Signal intensity decreases during SSNA increases occurred in the left orbitofrontal, frontal and right precuneus cortices. These data reveal for the first time, cortical and subcortical sites involved in generating SSNA changes during emotions. ► Skin sympathetic and brain activity were measured concurrently during emotions. ► Increased sympathetic activity was associated with changes in brain activity. ► Brain activity increased in the amygdala, pons, thalamus, accumbens, and cerebellum. ► Brain activity decreased in the orbitofrontal, frontal and precuneus cortices. ► These data reveal brain sites involved in generating autonomic responses during emotions.